Melville: His World and Work. By Andrew Delbanco. London: Picador, 2005, xxx + 415 pp. £25.00 (£9.99 pbk)/30.00 (16.00 pbk) - Lowe, Matthew Forrest (Literature and theology, 2006)
Ifgenerations of writers and critics have found substance for their own time in the work of Melville, his thought seems not only more relevant today, but portable: his reflections on obsessive quests, national destinies and religious ambition can be hoisted, aimed and thrown at political targets as readily as any whaling harpoon. A sampling of such thrusts, ranging from early comments on Melville and Moby-Dick to recent observations on the Ahab-like crusades of the Bush administration, serves to open Andrew Delbanco's biography of Melville. It is a literary biography, so the manner in which Melville employed his words and ideas—and the ways his words have been employed since his death—are of paramount importance.